KOMPETENSI PROFESIONAL GURU BK DALAM MERANCANG PEMBERIAN LAYANAN INFORMASI DI SMP PERTIWI 2 PADANG - Ratnasari, Luzi; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
The background this research by professional competence of counsellor in designing service delivery information at school is not in accordance with students needs. The purpose of this research to describe: 1) Professional competency counsellor in service delivery of aspects analysis of the students needs, 2) Professional competence counsellor in preparation program, 3) Professional competence counsellor review of aspects implementation plan and BK program. This research is quantitative descriptive, the population is all students SMP Pertiwi 2 Padang which 397. Techniques used random sampling members of population is 80 people. Results: 1) Professional competency of counsellor in service delivery of aspects analysis the students needs are pretty good category, 2) Professional competence counsellor preparation program are unfavorable category, 3) Professional competence of counselor in implementation plan BK programs quite well category. Based on the results of the study writer suggest to counsellor more active role in preparing the counselee analyze needs andÂ implementation of BK programs, and headmaster to be able to work with teachers in the implementation of BK program at school.